AdditiveChem: A comprehensive bioinformatics knowledge-base for food additive chemicals. (5th March 2020) - Zhang, Dachuan; Cheng, Xingxiang; Sun, Dandan; Ding, Shaozhen; Cai, Pengli; Yuan, Le; Tian, Yu; Tu, Weizhong; Hu, Qian-Nan
Abstract: Food additives are considered to be the catalysts and headstones of the modern food industry, affecting every step of food production, processing, and storage. The urgent need for a comprehensive curation of food additives, including their molecular structures, biological activities, and precise toxicological evaluations, prompted the creation of the AdditiveChem database (http://www.rxnfinder.org/additivechem/ ). This database has curated >9064 types of food additives, along with their molecular structure, chemical and physical properties, absorption, distribution, metabolism, excretion and toxicity properties, biosynthesis and biodegradation methods, usage specifications, toxicological and risk assessment data, and targets in the human body from 16 databases to construct an efficient search platform for in silico preliminary evaluations. AdditiveChem database will enable an exploration of the relationship between the structure and function of food additives. Highlights: AdditiveChem is a free, comprehensive, high-quality global food additive database Information was systematically gathered from 16 databases and prediction models AdditiveChem can be used in preliminary toxicology evaluations and docking studies